PENGARUH LINGKUNGAN KELUARGA DAN MEDIA PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA XI OTKP SMK BATIK SURAKARTA - Bangkit Choirun Nisa; Hery Sawiji; Susantiningrum Susantiningrum (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
Bangkit Choirun Nisa. K756015. THE EFFECT OF FAMILY ENVIRONMENT AGAINST AND LEARNING MEDIA TOGETHER TO THE INTEREST OF STUDENT LEARNING AT THE 11TH GRADE OF OTKP AT SMK BATIK SURAKARTA IN THE ACADEMIC YEAR OF 2020/2021. Skripsi, Faculty of Teacher Training and Education, University of Sebelas Maret Surakarta. Juny 2021. The purpose of this research is to find out: (1) the effect of family environment against to the interest of student learning at the 11th grade of OTKP at SMK Batik Surakarta in the academic year of 2020/2021; (2) the effect of learning media to the interest of student learning at the 11th grade of OTKP at SMK Batik Surakarta in the academic year of 2020/2021); and (3) and the effect of family environment against and learning media together to the interest of student learning at the 11th grade of OTKP at SMK Batik Surakarta in the academic year of 2020/2021. This study uses descriptive quantitative methods. The research population is used is all students of 11th grade of OTKP at SMK Batik 1 Suarakarta. Sampling technique is using saturation sampling with 54 students as samples. Data collection method using questionnaire, and document analysis. Data analysis is using multiple linear regression analysis with prerequisite analysis test i.e. normality test, linearity test, and multicollinearity test. The results of the study were as follows: (1) ) there is a positive and significant effect of family environment against to the interest of student learning at the 11th grade of OTKP at SMK Batik Surakarta in the academic year of 2020/2021 (tcount 2,297 < ttable 2,00758); (2) there is a significant and positive effect learning media to the interest of student learning at the 11th grade of OTKP at SMK Batik Surakarta in academic year 2020/2021 (tcount 6,153 < ttable 2,00758); and there is a positive and significant effect of family environment againts and learning media together to the interest of student learning at the 11th grade of OTKP at SMK Batik Surakarta in academic year 2020/2021 (Fcount 38,205 < Ftable 3,18).